Infrastructure development and the Indian economy - "Dash, L. N." (New Delhi, 2008)
Infrastructure represents the wheels of economic activity. Adequate infrastructure provision helps to diversify production, expand trade, cope up with population growth, reduce poverty', etc. There is a close link between infrastructure and development. A one per cent increase in the stock of infrastructure is associated with a one per cent increase in Gross Domestic Product (GDP). Infrastructure services also contribute to environmental sustainability. Adequate infrastructure services help to improve the quality of life of people. Despite its huge importance, minimum infrastructure services are still beyond the reach for millions of people in the world. About 1.1 billion people lack access to clean water supply and about 2.6 billion live with inadequate sanitation. At the same time 2-3 billion people lack access to modern energy and nearly 20 per cent of rural population reside more than 2 km. from an all-weather road. The various countries of the world have recognized the key role that infrastructure can play both directly and indirectly to achieve the socio-economic goals. India during the last one and a half decade is trying hard to improve in all spheres of economic activity and it is indeed in the path of rapid economic progress. Of late, planners and development economists have expressed concern about the adequacy of infrastructure facilities to sustain the tempo of economic progress. The book, therefore, focuses on such a burning topic to highlight the various strengths and weaknesses of infrastructure provision in India. It covers both economic and social infrastructure. The former includes public utilities such as transport, communication, energy, water supply, sanitation and the later covers education and health. The following is the chapter division: Introduction; Transport and Communication: Kingpin of Economic Development; Energy Infrastructure : Critical to India's Development; Water Supply and Sanitation Facilities in India; Education and Human Capital Base in India; Health Infrastructure in India; Dimensions of Infrastructure Financing in India.